Combined radiolarian-ammonite stratigraphy for the Late Jurassic of the Antarctic Peninsula: implications for radiolarian stratigraphy - Kiessling, Wolfgang (1999)
New biostratigraphic data from cooccurring radiolarians and ammonites in Upper Jurassic sequences of the Antarctic Peninsula (Byers Peninsula on Livingston Island and Longing Gap, Graham Land), permit a revised and more refined regional stratigraphy. The new data also allow a revision of the chronostratigraphic assignment of some American radiolarian zones established by Pessagno and collaborators: the boundary of Zone 34 is assigned to the latest Kimmeridgian, contrasting the former assignment to the early/late Tithonian boundary. The boundary between Subzone 4 beta and 4 alpha is assigned to the early Tithonian, but was usually correlated with the early late Tithonian/late late Tithonian boundary. The new chronostratigraphic data from Antarctica are used together with recent results of Baumgartner and collaborators to revise the age assignment of the North American Late Jurassic radiolarian zones.